Demulsifier Selection Based On The Evaluation Of Demulsification Performance Indicators - B. Pramudono; H. B. Mat (Dept. of Chemical Engineering, Diponegoro University, 2005)
A method for characterizing and selecting demulsifiers has been developed. The development was based on either the relationships between the demulsification parameters and demulsifier performance or demulsifier characteristics and demulsifier performance. The importance of each of these parameters to performance was discussed. The result was eight demulsification performance indicators consisting of the percentage of water separation, percentage of oil separation, demulsification efficiency, demulsification effectiveness, partition coefficient, interfacial pressure, interfacial activity, and Hydrophilic Balance (HLB). Quantification of the indicators conducted by determination of the performance indexes for each indicator. It was obtained from the condition that the demulsifier exhibits good performance. Additionally, the study found a correlation between the parameters it self. The demulsifier effectiveness as well as the interfacial pressure reaches a maximum value when the partition coefficient closed unity. Increasing of the interfacial pressure, in consequence, will increase both the demulsifier effectiveness and interfacial activity. The effect of both the HLB and molecular weight on the percentage of separation indicates a weak correlation.Keywords :A method for characterizing and selecting demulsifiers has been developed. The development was based on either the relationships between the demulsification parameters and demulsifier performance or demulsifier characteristics and demulsifier performance. The importance of each of these parameters to performance was discussed. The result was eight demulsification performance indicators consisting of the percentage of water separation, percentage of oil separation, demulsification efficiency, demulsification effectiveness, partition coefficient, interfacial pressure, interfacial activity, and Hydrophilic Balance (HLB). Quantification of the indicators conducted by determination of the performance indexes for each indicator. It was obtained from the condition that the demulsifier exhibits good performance. Additionally, the study found a correlation between the parameters it self. The demulsifier effectiveness as well as the interfacial pressure reaches a maximum value when the partition coefficient closed unity. Increasing of the interfacial pressure, in consequence, will increase both the demulsifier effectiveness and interfacial activity. The effect of both the HLB and molecular weight on the percentage of separation indicates a weak correlation.Keywords : Chemical demulsifier, demulsifier performance, demulsification parameters, performance index